Understanding Investigational Perspective of Antioxidant and Antibacterial Properties of Rice - Intan Farahanah; Shariza Sahudin; Hannis Fadzillah Mohsin; Siti Alwani Ariffin; Liyana Dhamirah Aminuddin (Rice Science)
Whole-grain rice has gained significant attention for its potential health benefits, particularly because of its antioxidant and antibacterial properties. Despite this growing interest, there remains a pressing need for a comprehensive evaluation of the methods used to analyze these bioactive compounds, considering the diversity of rice types and the influence of environmental factors. This review aims to provide an in-depth overview of recent analytical methods, particularly those employed over the last five years, to assess the antioxidant and antibacterial properties of rice. It focuses on commonly used antioxidant assays, such as the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity assay, which encompasses both single electron transfer and hydrogen atom transfer mechanisms. Other antioxidant assays are also discussed, alongside methods used to evaluate antibacterial properties, including disc diffusion, well diffusion, broth or agar dilution, and advanced techniques such as flow cytofluorometric and bioluminescent assays. The review further explores the bacterial strains most frequently studied, including Bacillus cereus, Listeria monocytogenes, Escherichia coli, and Salmonella species. It highlights the key techniques and parameters employed to ascertain and quantify the antioxidant and antibacterial potential of rice, while critically analysing the strengths and limitations of these approaches. By synthesizing current methods and offering insights into their application, this review can be served as a guide for future research aimed at standardizing and improving the assessment of rice’s bioactive properties, paving the way for broader scientific and practical applications.